Growth Response of Edamame Soybean Intercropped with Sweet Corn at Different Planting Dates - Hidayat Saputra; Zainal Mutaqin (Universitas Lampung, 2021)
The multiple cropping system is one of the cultivation systems that is suitable for increasing land productivity, especially those with low fertility levels. The main problem with the intercropping cropping pattern is competition between plants. The correct timing of planting can minimize the negative effects of competition between plants so that it can optimize plant growth and production. The purpose of this study was to determine the best planting time in the intercropping pattern of sweet corn and edamame soybeans. The treatments consisted of 4 types in planting time: edamame soybeans monoculture (T0), edamame soybeans were planted simultaneously with sweet corn (T1), edamame soybeans were planted 7 days before sweet corn (T2), and edamame soybeans were planted 14 days before sweet corn (T3). The results showed that the difference in planting time did not lead to suppress of the growth of edamame soybeans at different planting times with sweet corn in the intercropping system compared to monoculture system. So that we can apply the same planting time between edamame soybeans and sweet corn in intercropping system.Keywords: Ademame, growth, intercropping, optimize, planting time